2020
DOI: 10.1038/s41598-020-61912-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorhexidine mouthwash on the oral microbiome

Abstract: Following a single blind, cross-over and non-randomized design we investigated the effect of 7-day use of chlorhexidine (CHX) mouthwash on the salivary microbiome as well as several saliva and plasma biomarkers in 36 healthy individuals. They rinsed their mouth (for 1 min) twice a day for seven days with a placebo mouthwash and then repeated this protocol with CHX mouthwash for a further seven days. Saliva and blood samples were taken at the end of each treatment to analyse the abundance and diversity of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
185
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(195 citation statements)
references
References 36 publications
6
185
1
3
Order By: Relevance
“…Several previous studies have reported a detrimental effect of antibacterial chlorohexidine mouthwash on ONR capacity (Kapil et al 2013(Kapil et al , 2018Bondonno et al 2015;McDonagh et al 2015;Sundqvist et al 2016;Woessner et al 2016;Ashworth et al 2019;Bescos et al 2020). However, despite the established antimicrobial properties of chlorine, and contrary to our hypothesis, there was no difference between the abilities of swimmers and non-swimmers to form NO 2 − in the oral cavity when administered a NR mouth rinse.…”
Section: Discussioncontrasting
confidence: 81%
“…Several previous studies have reported a detrimental effect of antibacterial chlorohexidine mouthwash on ONR capacity (Kapil et al 2013(Kapil et al , 2018Bondonno et al 2015;McDonagh et al 2015;Sundqvist et al 2016;Woessner et al 2016;Ashworth et al 2019;Bescos et al 2020). However, despite the established antimicrobial properties of chlorine, and contrary to our hypothesis, there was no difference between the abilities of swimmers and non-swimmers to form NO 2 − in the oral cavity when administered a NR mouth rinse.…”
Section: Discussioncontrasting
confidence: 81%
“…• Potential negative impacts on beneficial aspects of the oral microbiome highlighted in recent evidence (e.g. impact on nitric oxide pathway) (Bescos et al, 2020).…”
Section: Available Evidencementioning
confidence: 99%
“…The decision to select a specific toothpaste or a mouth rinse should be also based on a combination of factors: Patient preferences including cost, taste, etc. Unwanted effects including staining, burning sensation during use, etc. Potential negative impacts on beneficial aspects of the oral microbiome highlighted in recent evidence (e.g. impact on nitric oxide pathway) (Bescos et al, 2020). Potential negative impacts on blood pressure: one short‐term (7‐days) study suggested a non‐statistically significant “trend” for chlorhexidine mouth rinse to cause a small elevation in systolic blood pressure from 103 mmHg to 106 mHg (Bescos et al, 2020).…”
Section: Clinical Recommendations: Supportive Periodontal Carementioning
confidence: 99%
“…Salvage from mouthwash use showed enhancement of the oral bacteria capable of reducing nitrate. Finally, Bescos et al demonstrated that chlorhexidine mouthwashes for 7 days led to a major shift in salivary microbiome resulting in more acidic conditions, lower nitrite availability and higher systolic blood pressure in healthy study subjects [74].…”
Section: Effects Of Antiseptic Mouthwashes On No Homeostasis and Morbmentioning
confidence: 99%